(untitled) (Global Journal of Human-Social Science, 2024)
This research investigates the importance of musical instruments emphasizing their role in expressing and preserving cultural identity It highlights their significance in conveying emotions playing ceremonial and ritualistic roles fostering social cohesion preserving traditions contributing to global music fusion impacting tourism and holding symbolism and spirituality The study then focuses on Bangladesh s rich history of musical instruments exploring the diverse heritage and cultural expressions aiming for a robust and credible exploration of the history and future of Bangla musical instruments The researcher interviewed critical stakeholders including artists musicologists lyricists tuners instrumentalists and media personnel A comprehensive literature review and the researcher s insider perspective from a government-owned radio organization provided additional insights Structured and semi-structured interviews were used for primary data collection employing qualitative analysis techniques The result is fascinating Half of the respondents believe Western musical instruments have increased in modern and folk music Nearly all respondents think acoustic and electric musical instruments are used more in our country The majority feel that using electric and Western musical instruments has positively changed Bengali music and the majority believe Western instruments have influenced Bengali songs